Daniel Christie: capstone - Christie, Daniel, artist (Colorado State University. Libraries, 2016)
The artist's statement: As an artist I tend to focus my attention on color and story. I consider myself to be a lover of both. I try to find ways to fit one or both culture and story into my design. This works much better for culture in the graphic arts, as I look for ways to communicate cross-culturally throughout my work. Some of the design work that I have done is in Arabic or Serbian, and for the latter I have designed a Cyrillic typeface to accompany one of my projects. I love maps and look for ways to incorporate an international/global aspect to my work. When thinking about an international audience, I take into account colors, moods, ways of expression and communication that may have different effects upon viewers from different backgrounds. Of course I cannot tailor my designs to all cultures at once, but if I can gage my potential audience, I can make myself aware of different perceptions towards design, or advertising in their culture. This thought that goes into my work undergirds it and holds everything together, in thinking about the viewer, client, or user.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design